The Effects of Stress and Social Support on Externalizing Behaviors Among Children in Military Families. Issue 3 (3rd March 2016) - Sumner, Jennifer; Boisvert, Danielle; Andersen, Judith P.
ABSTRACT: Drawing on social support theory, this study examines the main and interactive effects of parental perceived stress and social support on externalizing behaviors in military youth. Findings reveal that not only do social support and stress affect the conduct of military children, but social support also moderately buffers the effects of parental stress. Given the increasing distance between military and American culture, more generally, this research is one opportunity to make sense of contradictory expectations about the well-being of military youth. In doing so, it provides implications for how a more supportive organization can benefit military families.